ANALISIS MINAT DAN MOTIVASI BERWIRAUSAHA MAHASISWA DI UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA (UNSURYA) (Studi pada Mahasiswa Mata Kuliah Manajemen Bisnis Ritel, Kelas Reguler Pagi, Program Studi Akuntansi dan Manajemen Semester 4 Tahun Ajaran 2016/2017) - Nalurita, Sari (Feb Universitas Dirgantara Marsekal Suryadarma, 2017)
This research aims to 1) Know Entrepreneurship Motivation of Unsurya's Students and 2) Knowing the interest of Unsurya’s students in entrepreneurship. The method of this research was used qualitative research with descriptive approach, using primary data in the academic year of 2016/2017. Researcher took the regular Retailing Business Management class semesters 4 as the population with 14 students as the sample and taken by random sampling. The results showed that the average motivation of Unsurya’s students in entrepreneurship was 66.51 percent with the greatest motivation value is the ambition for freedom indicator that is equal to 75.71 percent, while the self realization value is 48.81 percent, while the pushing factor with a value of 75 percent. Analysis of Unsurya’s students interest in entrepreneurship is equal to 42,86 percent, while uninterested is 28,57 percent and still considering 28,57 percent. This shows that the interest of Unsurya students to the entrepreneur is significant. Keywords: Entrepreneurial Intention, Entrepreneurial Motivation, Entrepreneurship, Student